1991
DOI: 10.1007/bf00227322
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of rye (Secale cereale L.) Genetics of male sterility of the G-type

Abstract: The genetics and relationships between the genes in rye located in the nucleus and cytoplasm of the male sterility of the G-type were investigated. A factor inducing male sterility was found in the cytoplasms or rye cv Schlägler alt and rye cv Norddeutscher Champagner. Monogenic inheritance was observed in linkage tests. Using primary trisomies of rye cv Esto, the nuclear gene ms1 was found to be located on chromosome 4R. Modifying genes, probably masked in normal cytoplasm but expressed in male-sterility-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 3 publications
2
29
0
Order By: Relevance
“…A weak restorer gene for the G cytoplasm was also identified on the 6R chromosome by means of trisomics analysis (Melz and Adolf 1991). This result is consistent with the suggested localization of two RAPD markers (pr777/600 bp and pr433/ 800 bp) on the 6R chromosome.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…A weak restorer gene for the G cytoplasm was also identified on the 6R chromosome by means of trisomics analysis (Melz and Adolf 1991). This result is consistent with the suggested localization of two RAPD markers (pr777/600 bp and pr433/ 800 bp) on the 6R chromosome.…”
supporting
confidence: 87%
“…The existence of at least three loci for male sterility in cms-C cytoplasm is expected. Assuming that cms-G and cms-C cytoplasms are very similar (Warzecha and Salak-Warzecha 1996), it is reasonable to suggest that, except for the two genes on chromosomes 4R and 6R identified in this study, another locus for male sterility could be positioned on chromosome 3R (Melz and Adolf 1991).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Łapin´ski and Stojałowski (2001) found that the vast majority of male sterility sources from 50 rye populations belonged to the Vavilovii type. This also holds true for the G cytoplasm (Melz and Adolf 1991) that was used to produce a hybrid variety in Germany in 2000 (ÔNovusÕ).…”
mentioning
confidence: 85%